ER-associated degradation and disposal of misfolded GPI-anchored proteins in Trypanosoma brucei - Tiengwe,CW; Koeller,C; Bangs,J (Molecular Biology of the Cell, 2018)
Misfolded secretory proteins are retained by endoplasmic reticulum quality control (ERQC) and degraded in the proteasome by ER-associated degradation (ERAD). However, in yeast and mammals, misfolded glycosylphosphatidylinositol (GPI)-anchored proteins are preferentially degraded in the vacuole/lysosome. We investigate this process in the divergent eukaryotic pathogen Trypanosoma brucei using a misfolded GPI-anchored subunit (HA:E6) of the trypanosome transferrin receptor. HA:E6 is N-glycosylated and GPI-anchored and accumulates in the ER as aggregates. Treatment with MG132, a proteasome inhibitor, generates a smaller protected polypeptide (HA:E6), consistent with turnover in the proteasome. HA:E6 partitions between membrane and cytosol fractions, and both pools are proteinase K-sensitive, indicating cytosolic disposition of membrane-associated HA:E6. HA:E6 is de-N-glycosylated and has a full GPI-glycan structure from which dimyristoylglycerol has been removed, indicating that complete GPI removal is not a prerequisite for proteasomal degradation. However, HA:E6 is apparently not ubiquitin-modified. The trypanosome GPI anchor is a forward trafficking signal; thus the dynamic tension between ERQC and ER exit favors degradation by ERAD. These results differ markedly from the standard eukaryotic model systems and may indicate an evolutionary advantage related to pathogenesis.